Identifikasi Faktor-Faktor Yang Mempengaruhi Pemberian MP-ASI Dini Dan Susu Formula Pada Bayi Sebelum Usia 6 Bulan Di Klinik Pratama Evi - Manullang , Lesdi Citra Lamtama Br; Putri , Aulivia; Fikry , Mei Waddah Ayunda; Giawa, Aniria; Zai, Lismawarni; Nababan, Tiarnida (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Infant health is greatly influenced by optimal nutritional intake, particularly through exclusive breastfeeding for the first six months of life. However, the rate of exclusive breastfeeding in Indonesia, especially in North Sumatra and Evi Primary Clinic, is still low. Many mothers provide early complementary feeding and formula milk before the baby is 6 months old, which can increase the risk of health issues in infants. Objective: To identify and analyze the factors affecting early complementary feeding and formula milk use in infants under 6 months of age at Evi Primary Clinic. Method: This study uses a qualitative descriptive design with a phenomenological approach. Sampling was conducted through purposive sampling until data saturation was reached, with a total of 10 informants (mothers of infants under 6 months who provided complementary feeding/formula). Data were collected through in-depth interviews. Data analysis followed the Miles, Huberman, and Saldana (2024) model. Results: The analysis revealed three main themes: (1) The perception of insufficient breast milk as the primary trigger for providing complementary food/formula, (2) Socio-cultural pressure and advice from the nuclear and extended family (especially in-laws) that encourage early provision, and (3) The inconsistent dual role of health workers, ranging from those who support exclusive breastfeeding to those who recommend formula milk from the start. Factors such as mothers' low knowledge about exclusive breastfeeding, economic conditions, and mothers returning to work also played a role. Conclusion: The practice of providing early complementary foods and formula milk to infants under six months of age is influenced by a complex interaction of internal and external factors, with maternal perception, culture, and family support as the dominant factors. The implications of this research highlight the need for ongoing education involving families, consistent training for health workers, and supportive policies to enhance breastfeeding practices.